Physical Characteristic and Palatability of Bio-Supplement Biscuit for Dairy Goat - Retnani, Y; Permana, IG; Purba, LC (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
The objective of this study was to evaluate the physical characteristic and palatability of bio-supplement biscuit for dairy goat. This experimental research applied Completely Randomized Design, constituting 20 heads of dairy goat randomly assigned to five dietary treatments. The treatments were R1 = bio-supplement biscuit of Indigofera sp; R2 = bio-supplement biscuit of Sauropus androgynus L. Merr leaf; R3 = bio-supplement biscuit of Carica papaya L leaf; R4= bio-supplement biscuit of Sauropus androgynus L. Merr leaf and Indigofera sp; R5= bio-supplement biscuit of Carica papaya L leaf and Indigofera sp. The variables measured were moisture, water activity, water absorption, density, and palatability. The results indicated significant effect of bio-supplement biscuit treatment on water content, water absorption, density, and palatability, but no significant effect on water activity. Palatability of R1 was 76.38Â±7.92 g/head, R2 was 23.81Â±6.08 g/head, R3 was 40.25Â±3.54 g/head, R4 was 29.56Â±4.77 g/head, R5 was 95.63Â±7.36 g/head. Bio-supplement biscuit of Carica papaya L leaf and Indigofera sp had the highest values of dairy goatâs palatability for dairy goat, crude protein (36.65%) and density, but the lowest in water activity.Animal Production 15(2):83-88, May 2013